Transcriptomic and physiological biochemical analysis reveals the impact of polystyrene nanoplastics on the quality of nuts - Weijie Chen; Xiao Liu; Xuanzi Zhang; Ying Zhang; Xinyi Ma; Jiasheng Wu (Plant Stress)
Plastic, celebrated for its lightweight, durability, and cost-effectiveness, is widely used across industries, yet it also presents a significant risk to food safety. While many studies have looked at nanoplastics in crops, their effects on nuts remains unknown. In this study, we explored the potential effect of polystyrene nanoplastics (PS-NPs) on the nuts. Initially, we found that exogenously applied PS-NPs can penetrate and accumulate within the nuts of T. grandis. In addition, the accumulation of PS-NPs led to a decline in the length, width, and fresh weight of nuts. Furthermore, the accumulation of PS-NPs led to a decrease in the levels of key nutrients like starch, oil, and total phenols. The further exploration of its molecular mechanisms has revealed correlations between nut size and several pathways, include photosynthesis, riboflavin metabolism, and others. Further RT-qPCR analysis indicates that under SP-NPs stress, the expression of genes involved in starch biosynthesis, such as TgSUS, TgINV, TgENPP, and TgPK, decreased to varying degrees. In contrast, several genes involved in oil biosynthesis, including TgLACS, TgKASII, and TgDGAT, were upregulated. These findings indicate that PS-NPs have impacts on the T. grandis nuts at morphological, physiological, and molecular levels. In summary, this study has unveiled fresh perspectives on the potential harmful effects of PS-NPs on nuts.